Pengaruh Shift Kerja dan Persepsi Lingkungan Psikologis Tempat Kerja Terhadap Stres Kerja pada Perekam Medik - Riska Rosita - APIKES Citra Medika Surakarta (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2014)
In the golden age period, children are still in pre-operational thinking, that thinking at random, ambiguous, and not organized. At this age, visual perception is more effective and the child can maintain concentration for long periods of time. To form a skilled and intelligent child, it must be started early, by laying the foundations of knowledge which are easy to understand. One foundation of knowledge is to use color.The development of digital gaming continues to grow rapidly. Various genres appear according to the market needs, including, educational games. The game with the theme of education and provide interactive content for collaborative learning purposes. Through the game, then made the concept of Game Based Learning to meet the needs of education.To create an interactive game with users, especially children, the game requires an interaction between the components in the game. One form of interaction between components is using physics logic, ie an algorithm that allows the behavior of the components in the game like in the real world.Â Keywords: physics logic, digital game based learning, primary color education